The Enhanced Immune Protection in Small Abalone Haliotis diversicolor Against a Secondary Infection With Vibrio harveyi - Yao, Tuo; Lu, Jie; Bai, Changming; Xie, Zhilv; Ye, Lingtong (Frontiers in Immunology, 2021)
In recent years, more and more studies have shown that early pathogenic bacterial infection in invertebrates can enhance immunity and significantly reduce mortality when reinfected with the same pathogen. There are mechanisms to explain this phenomenon, but they are relatively few. In addition, dose-dependent primary infection is also associated with increased immunity. In the present study, the initial infection dose and mortality of abalone Haliotis diversicolor after reinfection with Vibrio harveyi were recorded, and the mechanism of immune enhancement was investigated by the transcriptomic response of abalone after two successive stimuli with V. harveyi. Priming with different concentrations of pathogen can enhance immunity; however, higher concentration is not always better. Compared with the first exposure, more genes were up-regulated after the second exposure. Among the commonly expressed genes, the immune related genes were significantly or persistently highly expressed after two infections and included pattern recognition receptors as well as immune effectors, such as toll-like receptors, perlucin 4, scavenger receptor class B-like protein, cytochrome P450 1B1-like, glutathione S-transferase 6, lysozyme and so on; in addition, these immune-related genes were mainly distributed in the pathways related to phagocytosis and calcium signaling. Among the specifically expressed genes, compared with the first infection, more genes were involved in the immune, metabolic and digestive pathways after the second infection, which would be more conducive to preventing the invasion of pathogens. This study outlined the mechanism of immune enhancement in abalone after secondary infection at the global molecular level, which is helpful for a comprehensive understanding of the mechanism of immune priming in invertebrates.